Status and Opinions of Public Health Centers and Industrial Dental Offices on the Oral Health Promotion of Korean Adult Workers - Sue-Hyang Lee; Soo-Myoung Bae; Bo-Mi Shin; Sun-Jung Shin (The Korean Society of Dental Hygiene Science, 2020)
Background: This study investigated the status of oral health promotion activities for adult workers in public health centers and industrial dental offices and provided basic data for the model development of oral health promotion program for adult workers in Korea.Methods: A questionnaire was developed separately according to the person who in charge of the oral health promotion activities in public health centers nationwide and dental hygienists working in 20 industrial dental offices. This survey was conducted through postal survey and consisted of 29 items and 35 items respectively, including 19 common items for general information, oral health promotion program status and opinion. Statistical analysis was performed using the IBM SPSS ver. 23.0.Results: We analyzed the data of 147 public health centers (57.9%) and 9 industrial dental offices (45.0%). A workforce with a lack of practice was the biggest barrier to oral health promotion activities for adult workers. However, both groups showed high intention for the practice of adult worker's oral health promotion activities. Also, they showed willingness to work together in an organic partnership to perform their roles (94.4% and 77.8%, respectively). Regarding the scope of cooperation in the implementation of the industrial oral health promotion activity linked to the public health center, dental hygienists of industrial dental offices responded that they could coordinate necessary matters and schedule management.Conclusion: The development of an oral health promotion program aided by the relationship between public health centers and industrial dental offices is essential for the oral health promotion of adult workers. The possibility of cooperation between the abovementioned centers was confirmed through this study. In a long-term perspective, it would be necessary to identify a method to institutionalize industrial dental hygienists for the provision of continuous oral health care in workplaces.